Ressignificando perdas: a Ginástica Feminina na perspectiva da mulher em processo de envelhecimento - Burti, Juliana Schulze (2018)
Pelvic floor dysfunctions, such as urinary incontinence (UI), are more common in women due to anatomy, pregnancies and births. The aging process increases the chances of these dysfunctions due to changes in involved systems, such as osteomuscular and genitourinary systems. Pelvic floor muscle training is recommended as the primary form of treatment, and postural stabilization exercises seem to maximize effects. There is little information about this approach to the general population, and many women do not even know the existence of the pelvic floor in their bodies. In addition there is a wrong knowledge in the population that losing urine is normal as you get older, and that aging is exclusively a phase of decline and loss. We presume that a specific exercise method, Women Gymnastics, can contribute to a re-signification of aging process in women. Five Women's Gymnastics meetings were held with women over 45 years of age, 20 women from the Open Maturity University of the Pontifical Catholic University of São Paulo (PUC-SP) and 23 from the Mary Mother Church, with a mean age of 68.5 and 63 years, respectively. The transcription of the speeches and a field diary were used for discursive analysis. The content was used to construct five thematic maps for each group, following the methodology proposed by Spink et al. (2014). Overall, the analyzes showed that women had little knowledge about the pelvic floor, but after the Women's Gymnastics, they all began to know the location, function and form of activation of this region of the body. Working the pelvic floor stimulated debates about sexuality and UI, and women reported improved UI symptoms after exercises. Both groups experienced difficulty in performing breathing exercises, but noticed improvement in posture. Group activities with theoretical and practical content that bring new information to aging women regarding their own body care, including the pelvic floor, can be an interesting alternative for health promotion and positivation of the aging process